ANALISIS PENGARUH SERAT POHON PISANG TERHADAP SIFAT MEKANIK DAN TOPOGRAFI PADA MATRIKS POLYESTER DENGAN 8 JENIS PISANG - Deni deni; Yuliyanto Yuliyanto; Juanda Juanda (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
This research was conducted to obtain data on mechanical ability in the form of tensile strength, impact strength and physical shape of 8 types of banana tree fibers using polyester matrix BQTN 157 with a volume fraction of 85%:15% made by hand lay-up method. The highest tensile voltage of composite fiber-based banana tree fibers random fiber arrangement is in the type of banana kepok with a volume fraction of 85% : 15% of 26.5 Mpa. And for the highest impact strength is on the type of banana kepok of 28.77 Kj/mm². As for the lowest tensile voltage reinforced fiber banana tree arrangement randomly that is on the type of banana honey with a volume fraction of 85% : 15% of 12.18 Mpa. And for the lowest impact force is in the banana type crew with a volume fraction of 85% : 15% of 15.13 Kj/mm²